A quantitative study of removal mechanism of copper polishing based on a single pad-asperity polishing test. (1st February 2023) - Zhou, Ping; Shi, Haosong; Wang, Lin; Hou, Changyu; Meng, Lei; Di, Hongyu; Guo, Dongming
Highlights: A new copper removal mechanism regarding external loads and reaction time. A model for decoupling the chemical and mechanical interactions in copper CMP. All model parameters can be experimentally calibrated. The first time to connect chrono-current to passivation layer growth. A novel method to monitor copper removal rate in CMP in real-time. Abstract: Continuous requirement for the improvement of chip performance caused an increasing attention on the copper polishing precision. To predict the copper removal rate, it is critical to understand the copper removal mechanism and quantitatively decouple the chemical and mechanical interactions. In this paper, the copper removal mechanism was investigated by a single pad-asperity polishing test with an in situ measurement device, which minimized the effects of random pad-asperity contact states and slurry distribution differences encountered in conventional experiments. Several electrochemical methods were used to monitor the chemical reaction rate and passivation processes, including the chrono-current method, electrochemical impedance spectroscopy (EIS) and X-ray photoelectron spectroscopy (XPS). The results reveal that mechanical action can hardly remove the unreacted copper. The complexing agent can only dissolve the mechanically removed passivation layer rather than dissolve the passivation layer directly. The copper is removed in an alternating process of generation and removal of passivation layers. A model is developed to predict the copper removal depth within 10% error. This research provides a quantitative analysis method for material removal rate of metal polishing. It can answer whether chemical reaction or mechanical action limits the improvement of removal rate or causes the change of removal rate. Graphical abstract: Image, graphical abstract